Studi Kajian Teori Perdagangan dan Implikasinya terhadap Kebijakan Pembangunan Negara Berkembang - Nia Safira Ramadhanty Pane; Rizky Amelia Siregar; Nurazizah Nasution; Alifia Haira Harahap (Universitas Kristen Indonesia Toraja, 2025)
International trade, involving interactions between nations, has now become critically important for the future growth and development sustainable. This study examines various trade theories, including absolute advantage, comparative advantage, and the Heckscher-Ohlin model, along with their effects on economic policies that promote growth. The analysis of these theories indicates that the outcomes of international trade have a significant impact on the development strategies of developing countries. This research underscores the crucial role of international trade in fostering economic growth in developing nations, such as Indonesia, through open trade policies that enhance exports and competitiveness. International partnerships, like the Belt and Road Initiative (BRI) between Indonesia and China, showcase considerable potential for improving infrastructure and connectivity, thereby supporting economic expansion and job creation. Nonetheless, challenges such as safeguarding domestic markets and ensuring the equitable distribution of trade benefits remain to be tackled. Consequently, developing nations need to design balanced trade policies that emphasize economic growth, sustainability, and social welfare, while continuously crafting adaptive strategies to navigate global changes.